Entrepreneurial participation depth on household risky financial asset allocation - Zhang, Limiao; Zhang, Wenjia; Wang, Yancong (The Economics and Finance Letters, 2023)
This paper aims to investigate the impact of entrepreneurial participation depth on household risky financial asset investments. The issue is examined using Probit and Tobit models based on the data of the 2017 China Household Financial Survey. First, the depth of entrepreneurial participation of entrepreneurs has a significant negative impact on whether their families participate in the risky financial market. Second, the more assets invested in entrepreneurship, the fewer households invest in risky financial markets. In addition, the depth of entrepreneurial participation would further squeeze out the degree of involvement in the risky financial market based on risk diversification and liquidity demand. Finally, the crowding out effect of entrepreneurial participation depth on household financial asset allocation differs between urban-rural duality and trust degree. This study further explains the mystery of limited participation in the risky financial market, helps understand the background risk characteristics of entrepreneurial families, promotes the scientific allocation of risky financial assets of related families and the stable operation of the risky financial market.